2016
DOI: 10.1016/j.jclinepi.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Selection bias was reduced by recontacting nonparticipants

Abstract: Objective: One of the main goals of health examination surveys (HES) is to provide unbiased estimates of health indicators at the population level. We demonstrate how multiple imputation methods may help to reduce the selection bias if partial data on some non-participants are collected. Study Design and Setting: In the FINRISK 2007 study, a populationbased health study conducted in Finland, a random sample of 10 000 men and women aged 25-74 were invited to participate. The study included a questionnaire data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
(45 reference statements)
0
28
1
Order By: Relevance
“…Due to these differences, health indicators estimated from the participants only are likely to suffer from selection bias. For example, recent results indicate that the true prevalence of smoking in Finland may be five percentage points higher than the prevalence based on the participants only [10].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Due to these differences, health indicators estimated from the participants only are likely to suffer from selection bias. For example, recent results indicate that the true prevalence of smoking in Finland may be five percentage points higher than the prevalence based on the participants only [10].…”
Section: Introductionmentioning
confidence: 90%
“…Re-contact data were collected in FINRISK 2007 and 2012 surveys where the main survey questionnaire was re-sent to non-participants. Although the response rates for the re-contact were very low, 13% and 14%, respectively, the re-contact data turned out to be useful in reducing selection bias [10,36]. It was found that when adjusted for age and sex, the re-contacted respondents tend to resemble the non-participants with respect to their mortality and hospitalizations.…”
Section: Re-contact Non-participantsmentioning
confidence: 97%
See 2 more Smart Citations
“…The decision about participation have been found to depend on the risk factors, such as smoking (Shahar et al, 1996), either directly or via a common cause such as health awareness. This may be deduced from the fact that the non-participants have a higher risk of death (Jousilahti et al, 2005;Harald et al, 2007;Karvanen et al, 2016). This dependence causes missing data to be classified as missing not at random (MNAR) (Rubin, 1976).…”
Section: Introductionmentioning
confidence: 99%